The Effect of Farmers’ Insurance-Adoption Behavior on Input for Beef-Cattle Disease Prevention: Endogenous Switching Regression Model - Liangying Zhang; Yunhua Wu (Agriculture)
This study selects the Inner Mongolia Autonomous Region (IMAR), among the most crucial beef-cattle farming areas in China, to obtain data from the micro-surveys of 447 beef-cattle farmers. Utilizing an endogenous switching regression (ESR) model, this research empirically investigates the effect of farmers’ beef-cattle insurance enrollment behavior on their input of disease prevention. This study finds that farmers adopting beef-cattle insurance reduce beef-cattle disease-prevention input. Based on counterfactual assumptions, if insured farmers had not adopted insurance, their input in disease prevention would increase by 33.45%. Further research confirms that a decrease in the market purchase price of beef cattle enhances the negative effect of farmers’ insured behavior on input for beef-cattle disease prevention. The heterogeneity analysis leads to two more conclusions. One is that insured farmers have the largest reduction in shed-disinfection input, the smallest reduction in voluntary vaccination input, and an intermediate reduction in deworming input. The other is that the act of adopting insurance reduces disease-prevention input to a greater extent for farmers who are far from the core areas of beef-cattle farming or who have not experienced beef-cattle deaths.